Familial Brachydactyly in an Indian Family: A case report - Halder, SK; Khan, I; Paira, SK; Mukherjee, R (Journal of Nepal Paediatric Society, 2011)
Brachydactyly or short digit is a rare deformity involving fingers and toes. We present a rare family with 6 known members affected with similar pattern of brachydactyly, affecting only bilateral index fingers. The knowledge of this entity is important and a thorough clinical and radiological evaluation is mandatory for any patient with digital deformities. DOI: http://dx.doi.org/10.3126/jnps.v31i3.5364 J Nep Paedtr Soc 2011;31(3): 241-243